Synthesis and characterization of Strontium Barium Niobate (SBN) ferroelectric thin films - Mendes, R. G.; Araújo, E. B.; Klein, H.; Eiras, J. A. (Boletín de la Sociedad Española de Cerámica y Vidrio, 1999)
Strontium barium niobate (SBN) thin films of good quality were deposited on Si and Pt/Si substrates using a polymeric resin produced by different starting precursors. Using X-ray diffraction, the presence of SBN phase could be identified for films annealed between 500-700ºC for 1 hour on both substrates. Undesired phases, such as SrNb2O6 and BaNb2O6, appear crystallized in films deposited on Si over annealing temperatures between 500-700ºC. However, these phases appear only at 500ºC for films deposited on Pt/Si. Dielectric characterization of SBN films indicated a dielectric constant 27 and dissipation factor of 0.047 at 100 KHz. Hysteresis loops were observed at room temperature for of SBN film annealed at 700ºC for 1 hour. At 100 Hz frequency, the remanent polarization, Pr, and the coercive field, Ec, were 18.4 mC/cm2 and 147.7 kV/cm, respectively. Las láminas delgadas de niobato de estroncio bario de buena calidad fueron depositadas sobre substratos de Si y Pt/Si mediante el empleo de una resina polimérica producida a partir de diferentes precursores. Por medio de difracción de rayos X se identificó la presencia de SBN para láminas tratadas entre 500-700ºC durante 1 hora sobre ambos substratos. Las fases no deseadas, como SrNb2O6 y BaNb2O6, aparecen cristalizadas en láminas depositadas sobre Si tratadas entre 500-700ºC. Sin embargo, estas fases aparecen solo a 500ºC para láminas depositadas sobre Pt/Si. La caracterización dieléctrica de las láminas de SBN presenta una constante dieléctrica de 27 y un factor de disipación de 0.047 a 100 kHz. Las curvas de histéresis fueron observadas a temperatura ambiente para láminas tratadas a 700ºC durante 1 hora. A la frecuencia de 100 Hz, la polarización remanente, Pr, y el campo coercitivo, Ec, fueron 18.4 mC/cm2 y 147.7 kV/cm, respectivamente.